PENGARUH RANGE OF MOTION (ROM) AKTIF KAKI TERHADAP RISIKO TERJADINYA ULKUS KAKI DIABETIK PADA PASIEN DIABETES MELITUS TIPE 2 DI PUSKESMAS RAMBUNG BINJAI - Sri Dewi Br. Siregar; Dady Hidayah Damanik; Suherni; Lilis Pujiati (Poltekkes Kemenkes Medan, 2025)
Active ROM foot exercises aim to improve blood circulation of the lower limbs, ankles, soles of the feet and fingers. Giving active ROM therapy can improve blood circulation in the feet and toes so that there is no tingling and numbness that causes diabetic foot ulcers. The purpose of this study was to prove the effect of active ROM of the foot on the risk of diabetic foot ulcers. This type of research uses quantitative research methods. With pretest-posttest control group design. The population was 117 people. The purposive sampling technique consists of 36 respondents and is divided into 2 groups, namely 18 control groups and 18 treatment groups, which have met the inclusion criteria. The results of the study in the treatment group showed that there was an effect before and after being given active ROM of the feet.